The Verb “Memukul’ in the Balinese Language Dialect Spoken at Taro Village: A Natural Semantic Metalanguage Study - Dian Saputra, Made; Suarka, I Nyoman; Cika, I Wayan (e-Journal of Linguistics, 2020)
The people living at Taro village speak the Balinese language as their daily language. As the speakers of the Balinese languge, they never neglect the speech order, as can be seen from the fact that they still use the Balinese words, which in the modern era, have been neglected, resulting in the fact that many people are not familiar with a number of words, especially those which belong to the verb word class, one of which is the verb “ngetok” (hit). The Balinese language has a great number of verbs; however, the current study only analyses the verb “ngetok’ (hit) using the theory of Natural Metalanguage Semantics (NMS). The verb “ngetok” (hit) has a great number of equivalents; they are ngebug, ngedig, nigtig, ngupek, megambel, mugpugin, mukpukin, ngukul, nungting, ngempug, nyakcak, noktok, ngeplokin, nebuk, ngaasin, nepung, ngintuk, ngalocok, namplak, nyemés, nempéléng, nyagur, nyepédin, nglamet, ngamplongin, ngamplengin, ngemplangin, nglentangin, ngaplekin, nyontok, nylimed and mentil . One verb is different from another, although they are all used to express the action of hitting something or someone, depending on what tool is used to hit and the subject and object which are hit. The verb “ngetok” (hit) in the Balinese language has two different meanings; namely doing something and taking place, which can be explained using the explication technique in which it is described that “X does something on Y, causing something either bad or good to occur to Y”. Such differences in meaning can be obtained through the analysis of the original meaning using the non-compositional polysemy